Investigating Brunei’s Seafood Markets for Vibrio parahaemolyticus using the Most Probable Number-Polymerase Chain Reaction - Murang, Zaidah Rizidah; Muharram, Siti Hanna; Abiola, Oduola Olakunte (Asian Journal of Medical Sciences, 2013)
Background: Vibrio parahaemolyticus (V. parahaemolyticus) is the commonest source of seafood poisoning and has a very high incidence in the countries of Asian. Aims and Objectives: This study aims to investigate the presence of V. parahaemolyticus in seafood from Brunei seafood market using the Most Probable Number- Polymerase Chain Reaction (MPN-PCR). Results: None of the twnety-three seafood samples that were purchased at random from unselectively chosen wet markets and hypermarkets in Brunei Darussalam yielded V. parahaemolyticus. Conclusion: This could be due to any or a combination of: the absence or low level of V. parahaemolytius from where the samples were harvested, inactivation of V. parahaemolyticus during the processing and preservation of the samples, possible sampling factors as well as good hygienic practices in Brunei’s seafood market DOI: http://dx.doi.org/10.3126/ajms.v5i2.8948 Asian Journal of Medical Science, Volume-5(2) 2014: 33-39